Exploración de los imaginarios sociales de la etnicidad garífuna - Randazzo Eisemann, Francesca; Coto Méndez, Ramón Fernando; Cacho Caballero, Xiomara Mercedes (CIICLA, Universidad de Costa Rica, 2021)
This article examines the Garifuna ethnic traits that contribute to the process of social cultural creation, which are possible to analyze from certain levels of registration of social imaginaries. In an attempt to collaborate in the elaboration of a Garifuna identity list, our main objective in this work is to address some fundamental dimensions of ethnic collectivities, in order to highlight them: a name, a common myth of ancestry, a common history, a shared culture, an association with a territory and a political movement to defend one's own identity. To fulfill this purpose, we essentially follow the guidelines of Anthony Smith (1987) and his collaborators. The work bases mainly on the deep founding myths as a way of studying Social Imaginaries, as well as some of the productions relative to the group.